The effect of exercise type on immunofunctional and traditional growth hormone - Consitt, Leslie A.; Bloomer, Richard J.; Wideman, Laurie (European journal of applied physiology, 2007)
The purpose of this study was to compare the growth hormone (GH) response, including the immunfunctional (IF) GH response, between an acute bout of aerobic and resistance exercise in the same subjects. Ten cross-trained males (24.3 +/- 1.2 years) performed both 30 min of continuous cycling at 70% of VO(2max), and intermittent free weight squatting at 70% of 1-RM, in a randomly assigned crossover design, separated by at least 1 week. Blood samples were collected at 10-min intervals for 2 h (30 min rest, 30 min exercise, 60 min recovery) and analyzed for total human and IF GH. After adjusting for the amount of work performed per minute of exercise, integrated GH AUC was significantly greater during the resistance session than the aerobic session as measured by both the total and IF GH assays (P = 0.008 and P = 0.014, respectively). Peak GH concentrations were significantly greater during the resistance session than the aerobic session (P = 0.05). A similar overall GH pattern was observed in response to both types of exercise, with peak values occurring at the end of exercise, regardless of the GH assay used. These data demonstrate that in young, cross-trained males, intermittent resistance exercise elicits a greater response of GH, including IF GH, compared to a continuous aerobic session, when controlling for the work performed per minute, intersubject variability, relative exercise intensity and session duration.